Correction: Hauck et al. Molecular Orbital Theory-Teaching a Difficult Chemistry Topic Using a CSCL Approach in a First-Year University Course. Educ. Sci. 2021, 11, 485 - David Johannes Hauck; Insa Melle; Andreas Steffen (MDPI AG, 2022)
Andreas Steffen was not included as an author in the original publication [...]